2016
DOI: 10.3904/kjim.2015.199
|View full text |Cite
|
Sign up to set email alerts
|

Blood count parameters can predict the severity of coronary artery disease

Abstract: Background/AimsBecause of the inflammatory nature of coronary artery disease (CAD), both platelets and white blood cells have been investigated for years. The aim of this study was to investigate the relationships between some prominently hematologic blood count parameters (mean platelet volume [MPV], neutrophil to lymphocyte ratio [NLR]) and the severity of CAD by using Gensini scores.MethodsA total of 194 patients, who had undergone coronary angiography, enrolled in this study. The control group consisted of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 32 publications
1
41
0
1
Order By: Relevance
“…Hematological abnormalities have been associated with coronary heart disease (CHD), oxidative damage, and other health problems. [1][2][3][4] Epidemiological studies have reported associations between an increased WBC count and the risk of CHD and subclinical atherosclerosis. 5,6 A high RBC count may be a symptom of a disease or disorder, although it does not always indicate a health problem, and health or lifestyle factors can also cause a high RBC count.…”
Section: Introductionmentioning
confidence: 99%
“…Hematological abnormalities have been associated with coronary heart disease (CHD), oxidative damage, and other health problems. [1][2][3][4] Epidemiological studies have reported associations between an increased WBC count and the risk of CHD and subclinical atherosclerosis. 5,6 A high RBC count may be a symptom of a disease or disorder, although it does not always indicate a health problem, and health or lifestyle factors can also cause a high RBC count.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are different views related to whether immunological parameters, inflammatory cytokines, and lipid peroxidization products have an effect on cIMT. Previous studies have generally focused on the key role of inflammation in CAD (13,27,28). In contrast to the key role played by neutrophils in particular in coronary events, it has been suggested that lymphocytes have a regulatory role in the inflammatory response and in atherosclerosis (13,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have generally focused on the key role of inflammation in CAD (13,27,28). In contrast to the key role played by neutrophils in particular in coronary events, it has been suggested that lymphocytes have a regulatory role in the inflammatory response and in atherosclerosis (13,27,28). It has also been emphasized that NLR is an indirect indicator of CAD and is an independent marker for adverse cardiac events and mortality in patients with stable CAD (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean platelet volume (MPV) is an indicator of platelet activity, where larger platelets are more active in terms of aggregation and thrombogenicity. NLR and MPV are not only associated with cardiovascular events but also are associated with the severity of atherosclerosis [3].…”
Section: Introductionmentioning
confidence: 99%